The dark side of competition: Gender differences - Chang, Simone; Kan, Kamhon; Zhang, Xiaobo (International Food Policy Research Institute, 2016)
The literature has placed great emphasis on the advantages of competition on market efficiency while ignoring the downside of competition on health. Using a natural experiment in Taiwan, we show that excessive competition comes at a health cost. In the late 1940s, half a million soldiers retreated to Taiwan from Mainland China after a civil war. They were initially not allowed to get married until the marriage ban was essentially lifted in 1959. As a large number of soldiers flooded the marriage market, men faced much stronger mating competition than before, which in turn increased the likelihood of male depression and mortality.